A discontinuity-capturing approach to the simulation of two-phase hydrogen flows - Capmany, Nicolás; Könözsy, László Z.; Sanders, Drewan S. (Elsevier, 2026)
This paper focuses on the development of a Godunov-type approach in the context of two-phase liquid hydrogen (LH2) flows for pipeline networks, implemented and verified in an in-house code. The motivation of this work is to overcome the uncertainties arising in the numerical prediction of thermo-fluid hydrogen dynamics due to its extreme properties at low temperatures. It has been found that the Godunov-type approach developed here reduces the average relative error to 1.90% compared to well-established benchmark problems for compressible fluid flows, including a case with a non-linear boundary condition treatment. The selected examples have industrial relevance for cryogenic management systems. The obtained numerical results provide a reference solution for two-phase hydrogen flows. They also suggest that this variant of the Godunov-type method could serve as a suitable solution to enhance the accurate prediction of thermo-fluid hydrogen dynamics and support the design process of LH2 infrastructure for net-zero aviation.
Keywords: Energy; 34 Chemical sciences; 40 Engineering; Liquid hydrogen; Pipeline; Hydrogen infrastructure; Two-phase flows; Homogeneous equilibrium; Computational fluid dynamics